(untitled) (REMUNOM, 2026)
This study applies Newton’s Law of Cooling to evaluate the thermal performance of vacuum flasks using an Arduino-based data acquisition system. In this context, their applicability can be verified in numerous scenarios, contributing to advancements in science and technology. Accordingly, Two experiments monitored temperature decay over 24 hours, this work proposes an application of differential equations, particularly, revealing significant differences in heat retention among three flasks. Newton’s Law of Cooling, to evaluate different vacuum flasks, employing Arduino as a prototyping platform for data acquisition. This approach provides a practical demonstration of Exponential fits yielded R² > 0.996, confirming model validity. Newton’s Law of Cooling in the analysis of thermodynamic phenomena.